2005
DOI: 10.1002/bjs.4983
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of routine preoperative duplex imaging before varicose vein surgery

Abstract: Routine preoperative duplex examination led to an improvement in results 2 years after surgery for patients with primary varicose veins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 32 publications
2
27
0
Order By: Relevance
“…Yet, new data emphasises the importance of Duplex-derived information over hand-held Doppler (18). Indeed, our data supported the use of Duplex as au seful tool in assessment of axial reflux and its ablation.The axial superficial reflux plays am ajor role in deterioration of chronic venous insufficiency and development of skin lesions (23).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Yet, new data emphasises the importance of Duplex-derived information over hand-held Doppler (18). Indeed, our data supported the use of Duplex as au seful tool in assessment of axial reflux and its ablation.The axial superficial reflux plays am ajor role in deterioration of chronic venous insufficiency and development of skin lesions (23).…”
Section: Discussionsupporting
confidence: 70%
“…The advantage of visualising the vein and being able to investigate its haemodynamics over plain clinical examination should be obvious, but the evidence of the benefito fp reoperative Duplex evaluation is still contradictory (17,18 The patient characterisation by preoperative CEAP classification (19) was not possible as to the anatomy,because the objective haemodynamic informationo ft he patients treated in GSS was not available. The patients with severe venous insufficiencya ccording to C-classification were overrepresented in VSS (Table 1.)…”
mentioning
confidence: 99%
“…The authors reported previously that the rate of recurrence and reoperation 2 years after varicose vein surgery was lower with preoperative duplex examination than without 4 . A major reason was that incompetence in the great saphenous vein (GSV) or small saphenous vein (SSV) was often missed in the group without preoperative duplex imaging.…”
Section: Introductionmentioning
confidence: 92%
“…One reason is inadequate surgery owing to inadequate preoperative investigation 4 . The use of duplex ultrasound imaging before surgery has increased 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…These clinical signs of chronic venous insufficiency occur because of ambulatory venous hypertension resulting from venous reflux, due to either abnormal dilatation of the superficial veins (primary venous insufficiency) or deep vein thrombosis, valvular incompetence and reflux through the perforating veins (secondary venous insufficiency) 4 . Duplex imaging of venous reflux is the standard diagnostic procedure to assign the best surgical approach to varicose veins 5 but so far its value in the pathogenetic classification of the disease is limited. The cause of primary venous insufficiency remains largely unknown, but abnormal distensibility of the veins has been described 6,7 .…”
Section: Introductionmentioning
confidence: 99%